UNGKAPAN-UNGKAPAN METAFORIS DALAM PUISI-PUISIKARYA AGUS R. SARDJONO - Supriyadi Suriyadi (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2013)
This study aims to describe metaphorical expressions in Agus R. Sardjono’s poems that represent human perception space. This was a qualitative descriptive study. The data source was Suatu Cerita dari Negeri Angin, an anthology of poems written by Agus R. Sardjono, consisting of 39 poems. The research stages included: (a) metaphorical symbolidentification, (b) segmentation unit marking, and (c) metaphorical meaning description based on Halley’s classification. The findings show that in Agus R. Sardjono’s poems, there are symbols of metaphorical expressions representing human perception space. There are65 symbols of metaphorical expressions spread in nine types of human perception space. The metaphorical expressions are intended to obtain ethical and aesthetical effects in the poems. These two effects are presented through the use of metaphorical expressions symbolizing something concrete with an abstract purpose or, on the contrary, an abstract purpose using concrete symbols.